Analisis Dampak Pelaksanaan Webinar Terhadap Literasi Keuangan Pada Peserta Webinar Nasional Investasi Saham - Maha Martabar Mangatas Lumbanraja; Rahmat Junaidi; Sri Wahyuni Wildah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The capital market has been known as an alternative financing and investment in various countries with the presence of the Stock Exchange, but the initial findings from the study show that knowledge of alternative financing and investment (known as Financial Literacy) in developed and developing countries still shows significant differences. The role of Financial Literacy in creating economic growth in a nation is currently being observed by a number of academics, where it is clearly seen that countries with better levels of financial literacy will tend to develop more than countries with lower levels of financial literacy. Indonesia's financial literacy level which is still lower than neighboring countries such as Australia, Malaysia and Singapore in 2014 indicates the need for a number of ways that must be done, one of which is through the role of universities and organizational bodies under them to carry out this educational function. This research was conducted to determine the impact of the implementation of one of the webinars conducted by the Investment Gallery, Riau University with the theme